Development of Geoarcala Roblox Game Integrating Ethnomathematics of Magelang Temples to Enhance Critical Thinking Ability - Farid Azhar; Nina Agustyaningrum; Yesi Franita (Universitas Pendidikan Mandalika, 2026)
The ability to think critically is a vital skill in mathematics education. However, abstract and insufficiently contextualized instruction, especially in circular solid such as cylinders, hinders its optimal development. Integrating local cultural contexts through an ethnomathematics approach into game-based learning media offers a potential solution. This research intends to generate a learning game integrated within Roblox, namely Geoarcala, that integrates the ethnomathematics of temples in Magelang, and to evaluate its validity, practicality, and effectiveness in enhancing students’ critical thinking ability. A Research and Development (R&D) design incorporating the ADDIE framework was utilized. The participants included 23 ninth-grade students from class IX A at SMP Negeri 1 Salaman. Data collection methods comprised interviews, questionnaires, and tests. The validation results indicated that the media was valid (85.16% by content experts and 80.42% by media experts). The practicality test showed very practical results based on student (83.85%) and teacher (85%) responses. A paired-samples t-test revealed significant media effectiveness (t=10.68 and df = 22, p = 0.001, Cohen's d = 2.227). The average N-Gain score of 0.30 shows a moderate degree of improvement. These result indicate that the Geoarcala game is valid, highly practical, and shows moderate potential for enhancing students’ critical thinking ability.